2020
DOI: 10.1074/jbc.ra120.013751
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of the αM4 transmembrane helix in the muscle nicotinic acetylcholine receptor probed through mutagenesis and coevolutionary analyses

Abstract: The activity of the muscle-type Torpedo nicotinic acetylcholine receptor (nAChR) is highly sensitive to lipids, but the underlying mechanisms remain poorly understood.  The nAChR transmembrane α‑helix, M4, is positioned at the perimeter of each subunit in direct contact with lipids and likely plays a central role in lipid-sensing.  To gain insight into the mechanisms underlying nAChR lipid-sensing, we use homology modeling, co-evolutionary analyses, site-directed mutagenesis and electrophysiology to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Thus this study reveals that the expression system is fundamental to the observed effect of at least some pLGIC mutations, indicating that not only the amino acid composition but also the environment contributes to M4 behavior. These data explain the discrepancies previously observed between cationic pLGIC M4 helices, where some Ala mutations in 5-HT 3 A and α4β2 nACh receptor M4s can completely abolish channel function (assayed in HEK cells) ( Mesoy et al, 2019 ; Mesoy and Lummis, 2021 ), whereas Ala mutations in other pLGIC are rarely inhibitory and often cause small gains in function (assayed in Xenopus oocytes) ( Hénault et al, 2015 ; Cory-Wright et al, 2018 ; Tang and Lummis, 2018 ; da Costa Couto et al, 2020 ; Thompson et al, 2020 ) . Our data could also apparently explain discrepant studies showing that the C-terminal end of M4 can be deleted without affecting function in both ELIC ( Hénault et al, 2015 ) and Torpedo nACh receptors ( Tobimatsu et al, 1987 ) (data from oocyte expression), but other reports from receptors expressed in HEK cells suggest that cationic pLGICs do require the M4 C-terminus e.g., ( Butler et al, 2009 ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus this study reveals that the expression system is fundamental to the observed effect of at least some pLGIC mutations, indicating that not only the amino acid composition but also the environment contributes to M4 behavior. These data explain the discrepancies previously observed between cationic pLGIC M4 helices, where some Ala mutations in 5-HT 3 A and α4β2 nACh receptor M4s can completely abolish channel function (assayed in HEK cells) ( Mesoy et al, 2019 ; Mesoy and Lummis, 2021 ), whereas Ala mutations in other pLGIC are rarely inhibitory and often cause small gains in function (assayed in Xenopus oocytes) ( Hénault et al, 2015 ; Cory-Wright et al, 2018 ; Tang and Lummis, 2018 ; da Costa Couto et al, 2020 ; Thompson et al, 2020 ) . Our data could also apparently explain discrepant studies showing that the C-terminal end of M4 can be deleted without affecting function in both ELIC ( Hénault et al, 2015 ) and Torpedo nACh receptors ( Tobimatsu et al, 1987 ) (data from oocyte expression), but other reports from receptors expressed in HEK cells suggest that cationic pLGICs do require the M4 C-terminus e.g., ( Butler et al, 2009 ).…”
Section: Discussionsupporting
confidence: 67%
“…An extensive investigation of the bacterial pLGICs, ELIC ( Erwinia ligand-gated ion channel), and GLIC ( Gloeobacter ligand-gated ion channel) showed that many Ala M4 substitutions are detrimental to channel function in GLIC, but beneficial in ELIC ( Hénault and Baenziger, 2017 ). Similar experiments in anion-selective pLGIC M4s follow the GLIC pattern ( Cory-Wright et al, 2018 ; Tang and Lummis, 2018 ), while the α7 nACh receptor broadly shows an ELIC-like pattern ( da Costa Couto et al, 2020 ), as does the muscle nACh receptor α subunit ( Thompson et al, 2020 ), although the latter contributes only two subunits to the heteropentamer. This led to the proposal that there are two different pLGIC archetypes, depending on the importance of TMD interactions versus M4 flexibility ( Therien and Baenziger, 2017 ).…”
Section: Introductionmentioning
confidence: 58%
“…Anion-selective pLGIC M4s follow the GLIC pattern, , and early studies suggested that cation-selective pLGIC M4s might follow the ELIC pattern . However, results are not completely consistent as Ala mutations in the 5-HT 3 AR M4 have limited or detrimental effects on channel function, and data from the α subunit of the muscle nAChR shows some mutations are beneficial and some are detrimental to function, though these mutations were only present in 2/5 subunits, as opposed to 5/5 for the α7 nAChR and 5-HT 3 AR mutations.…”
Section: Introductionmentioning
confidence: 98%
“…However we note that the ELIC and nAChR studies were performed in Xenopus oocytes, and the other four in HEK293 cells, indicating that the requirement for the C-terminal domain may be more a function of the expression system than of the specific channel. An exception to this pattern is that alanine mutations in the M4 of the α subunit of the muscle nAChR expressed in oocytes show both gains and losses of function (Thompson et al, 2020). We note that these mutations are only present in 2 out of 5 subunits per channel, and what would happen in a muscle AChR with all 5 positions mutated is as yet unknown.…”
Section: Rescue Of Non-functional Receptorsmentioning
confidence: 69%